2019
DOI: 10.1037/aca0000182
|View full text |Cite
|
Sign up to set email alerts
|

A conditional threshold hypothesis for creative achievement: On the interaction between intelligence and openness.

Abstract: Theoretical perspectives on creativity have suggested that intelligence is necessary but not sufficient for creative behavior. Known as the threshold hypothesis, this idea has generated both controversy and confusion since Guilford (1967) suggested that creativity and intelligence would be correlated more strongly among those low in intelligence relative to those high in intelligence. In this article, we instead argue for a conditional threshold hypothesis such that the relationship between intelligence and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
(132 reference statements)
1
17
0
Order By: Relevance
“…Relatedly, other complex interactive effects could be investigated. For example, Harris et al ( 2019 ) proposed that the relationship between creative achievement and intelligence would be moderated by openness to experience. Hence, openness could also be considered as a moderator of the correlation between DT and intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, other complex interactive effects could be investigated. For example, Harris et al ( 2019 ) proposed that the relationship between creative achievement and intelligence would be moderated by openness to experience. Hence, openness could also be considered as a moderator of the correlation between DT and intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Thresholds suggest a qualitative difference of humans below and above the value that is implausible with respect to creativity and intelligence in specific but also, more generally, for psychological dispositions. Even more nuanced approaches—such as the conditional threshold theory ( Harris et al 2019 ), that supposes that openness plays a critical role in the intelligence-creativity threshold—are adding further complexity and researcher’s degrees of freedom. There are additional shortcomings of the prevalent data analytical strategy, such as violated model assumptions (e.g., normally distributed and homoscedastic residuals; Gelman and Hill 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding its links with intelligence, the results obtained to-date are quite heterogeneous. While some studies observed nearzero links (Kaufman et al 2014), others reported small-to-moderate correlations of r = .14 (Carson et al 2005;Harris et al 2019) and r = .23 (Kéri 2011) to quite robust associations of β = .29 (Beaty et al 2014) and r = .34 (Mar et al 2006). A recent longitudinal study (Karwowski et al 2017) that predicted CAQ scores in middle age (52 years old) by intelligence measured at age 11 and 13 showed negligible correlations with Raven matrices (r = .05, p = .047, N = 1594) and Wechsler Intelligence Scale for Children (r = .09, p = .077, N = 255).…”
Section: Caq and Icaa-a Closer Lookmentioning
confidence: 97%